EFEKTIVITAS DALAM PEMANFAATAN ALOKASI DANA BANTUAN OPERASIONAL SEKOLAH DI KABUPATEN TAKALAR - Nurfadila, Nurfadila; Abdi, Abdi; Syukri, Syukri (Universitas Muhammadiyah Makassar, 2024)
The purpose of this study was to determine the constraints faced by the Inspectorate in supervising the utilization of BOS allocations in Takalar District. This study uses qualitative methods. Data collection techniques are carried out using data reduction techniques, data presentation, data verification and drawing conclusions. The results of the study show that the level of effectiveness of Inspectorate supervision is through four indicators, namely: 1) Productivity in managing BOS funds has been able to achieve the supervision target for the inspectorate by complying with applicable SOP audits, reviews and surveys. 2) Adaptability in the communication aspect in the management of BOS funds is still not going well. 3) Job Satisfaction is still experiencing a low level of satisfaction, the main factor of dissatisfaction experienced is derived from the aspect of ability. 4) The search for resources is not yet sufficient, this can be measured from the education level of the Inspectorate staff in Takalar Regency.